The effect of enteral nutrition strategy and non-invasive ventilation on diarrhea and nutritional goals in the critically ill: A protocol for a multicentre retrospective cohort study (ENND GOALS) - Justin Bruni Senecal; Taiya Lakhanpal; Lawrence Mbuagbaw; Tatianna Giannidis; Parsa T. Khazaneh; Bram Rochwerg; Simon J.W. Oczkowski; Deborah J. Cook; Jennifer L.Y. Tsang; M. Ines Pinto-Sanchez; Sameer Sharif; David Armstrong; et al. (PLoS ONE, 2025)
Enteral nutrition (EN) has become the standard of care for nutritional support among critically ill patients. However, little is known about whether continuous delivery (CEN) or intermittent delivery (IEN) is preferable or the consequences of either strategy. This is particularly true for diarrhea, which is understudied but consistently shown to be associated with increased morbidity among critically ill patients. This is a multicenter, retrospective cohort study including critically ill patients greater than 18 years of age, admitted to the Intensive Care Unit in Hamilton, Canada, and prescribed EN for greater than 48 hours. Patients will be divided into IEN and CEN groups based on the nutritional strategy they received during their stay. The primary outcome will be the proportion of patients in each group with diarrhea during their ICU stay, diarrhea will be defined according to WHO criteria. Multivariate logistic regression will be performed to identify the role of covariates in the risk of developing diarrhea. Secondary outcomes will include caloric intake, incidence of ICU-acquired infections, including Clostridioides difficile, length of stay, and mortality. This study protocol has been approved by the Hamilton Integrated Research Ethics Board (#16453). The study findings will be disseminated at academic conferences and published in peer-reviewed journals.